2016
DOI: 10.1002/smll.201503392
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Dye Release from Mesoporous Silica-Based Imaging Probes Facilitates Long-Term Optical Tracking of Cell Populations In Vivo

Abstract: Nanomedicine is gaining ground worldwide in therapy and diagnostics. Novel nanoscopic imaging probes serve as imaging tools for studying dynamic biological processes in vitro and in vivo. To allow detectability in the physiological environment, the nanostructure-based probes need to be either inherently detectable by biomedical imaging techniques, or serve as carriers for existing imaging agents. In this study, the potential of mesoporous silica nanoparticles carrying commercially available fluorochromes as se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…Namely, a higher amount of hydrophobic cargo loading would lead to an increased hydrophobicity of the overall drug carrier system, which could have implications on the release rate in terms of delayed release [38] with increased loading of hydrophobic agents. Consequently, a higher loading degree could provide a release of cargo over a prolonged period of time [39]. In our earlier studies, we have clearly observed a delayed but efficient intracellular release within a couple of days [37,39] when using hydrophobic dye molecules at a loading degree of 5 wt %, in spite of hardly any release taking place under in vitro conditions in buffer solution only over a time course of one week [22].…”
Section: Resultsmentioning
confidence: 99%
“…Namely, a higher amount of hydrophobic cargo loading would lead to an increased hydrophobicity of the overall drug carrier system, which could have implications on the release rate in terms of delayed release [38] with increased loading of hydrophobic agents. Consequently, a higher loading degree could provide a release of cargo over a prolonged period of time [39]. In our earlier studies, we have clearly observed a delayed but efficient intracellular release within a couple of days [37,39] when using hydrophobic dye molecules at a loading degree of 5 wt %, in spite of hardly any release taking place under in vitro conditions in buffer solution only over a time course of one week [22].…”
Section: Resultsmentioning
confidence: 99%
“…A) The cells were visible for a period of 32 d. B,C) Ex vivo imaging of isolated organs verified tumor labeling and allowed for the detection of metastatic colonies. Reproduced with permission . Copyright 2016, Wiley‐VCH.…”
Section: In Vivo Imaging Of Silica‐based Materialsmentioning
confidence: 99%
“…Nanoscopic imaging probes have already made significant progress in overcoming limitations associated with conventional, molecular imaging agents . The nanostructures essentially can be either (1) inherently detectable by optical and biomedical imaging techniques, or (2) serve as carriers for existing, molecular imaging agents . Inorganic nanostructures are readily utilized as biomedical imaging probes due to their inherent detectability by a variety of different imaging modalities, for example, quantum dots, QDs, for optical imaging and superparamagnetic iron oxides, SPIONs, for magnetic resonance imaging (MRI).…”
Section: Nanotechnology As An Enabling Tool In Drug Developmentmentioning
confidence: 99%
“…With respect to drug delivery to inflammatory bowel diseases such as ulcerative colitis, novel material‐based rectal formulations have shown successful facilitation of mucosal healing by using drugs in hydrogels to target the inflamed colonic mucosa or thermo‐sensitive polymer platforms in murine models of colitis. Development and use of in vivo diagnostic imaging modalities is essential to follow effects of drugs and disease progression over time, for example, for intestinal inflammation by optical imaging and PET or optical imaging of cancer growth . A crucial challenge in utilizing nanodiagnostics if the nanoparticles carry the diagnostic probe is particle integrity (e.g., that the label remain attached to the particle during imaging).…”
Section: Model Systems To Decipher Mechanisms Of Disease For Drug Scmentioning
confidence: 99%
See 1 more Smart Citation